Indian Democracy and the Anti-Defection Law: Constitutional Perspective and Practical Challenges: भारतीय लोकतंत्र और दल-बदल कानून: संवैधानिक परिप्रेक्ष्य और व्यावहारिक चुनौतियाँ - Nair, Anila; Nama, Deepak (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This research paper presents a constitutional and political analysis of India’s anti-defection law, examining trends in political defection, instances of the formation and collapse of governments, party discipline, and the role of the judiciary from the first general election in 1952 up to 2025. In the context of growing political instability in India, the anti-defection law was enacted in 1985 as the Tenth Schedule to the Constitution and was further strengthened by the 91st Constitutional Amendment in 2003. These amendments aimed to curb the increasing incidents of defection and to bring stability to the democratic system. However, even up to 2025, several practical challenges persist, such as the partisan role of the Speaker, delayed decisions on defection petitions, excessive use of the party whip, and the erosion of legislators’ individual freedom of decision-making. Recent judicial pronouncements and new rules framed by states such as Jammu and Kashmir clearly indicate the need for reforms in the existing law. Against this background, the paper offers concrete suggestions for necessary structural and procedural reforms in the anti-defection law to strengthen Indian democracy. Abstract in Hindi Language: यह शोध-पत्र भारत के दल-बदल कानून का संवैधानिक और राजनीतिक विश्लेषण प्रस्तुत करता है, जिसमें 1952 के प्रथम आम चुनाव से 2025 तक दलबदल की प्रवृत्ति, सरकारों के गिरने-बनने की घटनाएँ, दलगत अनुशासन तथा न्यायपालिका की भूमिका का अध्ययन शामिल है। भारत में राजनीतिक अस्थिरता के बढ़ते संकट के बीच 1985 में दसवीं अनुसूची के रूप में दलबदल-विरोधी कानून लागू किया गया और बाद में 2003 के 91वें संशोधन से इसे और सुदृढ़ किया गया। इन संशोधनों का उद्देश्य दलबदल की बढ़ती घटनाओं को रोकना और लोकतांत्रिक व्यवस्था में स्थिरता लाना था। फिर भी 2025 तक ऐसी कई व्यावहारिक चुनौतियाँ बनी हुई हैं, जैसे—स्पीकर की पक्षपातपूर्ण भूमिका, दलबदल याचिकाओं पर विलंबित निर्णय, व्हिप का अत्यधिक उपयोग, और विधायकों की व्यक्तिगत निर्णय स्वतंत्रता का ह्रास। हाल के न्यायालयीन निर्णयों तथा जम्मू-कश्मीर जैसे राज्यों द्वारा बनाए गए नए नियम स्पष्ट करते हैं कि मौजूदा कानून में सुधार की आवश्यकता है। इस पृष्ठभूमि में यह शोध-पत्र भारतीय लोकतंत्र को मजबूत बनाने हेतु दलबदल कानून में आवश्यक संरचनात्मक व प्रक्रियागत सुधारों के ठोस सुझाव प्रस्तुत करता है। Keywords: दलबदल-विरोधी कानून, दसवीं अनुसूची, दलबदल, 52वाँ संविधान संशोधन, 91वाँ संविधान संशोधन, स्पीकर का विवेकाधिकार, न्यायिक समीक्षा, राजनीतिक स्थिरता।